Nutrient variability in phloem: examining changes in K, Mg, Zn and Fe concentration during grain loading in common wheat (Triticum aestivum). Issue 4 (23rd May 2014) - Palmer, Lachlan J.; Palmer, Lyndon T.; Rutzke, Michael A.; Graham, Robin D.; Stangoulis, James C. R.
<x xml:space="preserve">Abstract</x> In wheat, nutrients are transported to seeds via the phloem yet access to this vascular tissue for exudate collection and quantitative analysis of elemental composition is difficult. The purest phloem is collected through the use of aphid stylectomy with volumes of exudate collected normally in the range of 20–500 nl. In this work a new method using inductively coupled plasma mass spectroscopy (ICP‐MS) was developed to measure the concentration of K, Mg, Zn and Fe in volumes of wheat (Triticum aestivum, genotype Samnyt 16) phloem as small as 15.5 nl. This improved method was used to observe changes in phloem nutrient concentration during the grain loading period. There were statistically significant increases in phloem Mg and Zn concentration and a significant decrease in K over the period from 1–2 days after anthesis (DAA) to 9–12 DAA. During this period, there was no statistically significant change in phloem Fe concentration.